SEARCH FOR WAYS TO DETERMINE THE METHODOLOGICAL BASIS FOR RESEARCHING THE MENTAL HEALTH OF STUDENTS IN HIGHER EDUCATION INSTITUTIONS - Семиченко, Валентина; Лузік, Ельвіра; Артюшина, Катерина (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
The article is devoted to a topical issue – determining the methodological, theoretical, and methodical basis for organizing a system aimed at supporting and preserving the mental health of university students in a crisis society. Based on the analysis of scientific literature, the difficulties associated with solving this problem are highlighted. First of all, these include the lack of a clear theoretical basis for defining the concept of mental health, the multifaceted nature of the issues that need to be resolved, and inconsistency within the methodological basis. This necessitates the development of a theoretical model on systemic principles, the creation of a clear set of diagnostic tools, and the development of an effective support program. Based on the theoretical analysis, the content of the theoretical model of mental health has been determined. The model includes seven subsystems: physical, psychophysiological, mental, psychological, social, professional, and spiritual health. Mental health is the result of the integration of these subsystems, and it determines an individual’s overall attitude toward life. On this basis, the content and indicators for assessing the development of each subsystem have been identified, and appropriate diagnostic methods have been selected. It has been proven that conducting a full assessment requires considerable time and creates excessive strain on respondents. Therefore, it is more appropriate to use a support program that includes an initial diagnosis which (with a limited number of indicators) identifies the most vulnerable individuals and groups and serves as a foundation for developing forms of psychological support.